The Role of Sustainable Accounting in Managing the Financial Position to Support the Sustainable Development of Financial Companies in Iraq - Lecturer: Youssef abdel salam abdi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Purpose: This study aimed to find out how Iraqi companies use sustainable management accounting techniques (MATs). The study also looked at MATs' contribution to sustainable development.Theoretical framework: The three aspects of sustainability—integrative, social, and environmental—are the basis for the research, which examines the effects of numerous variables, such as the frequency of technique use.Design/methodology/approach: The purpose and frequency of usage of sustainable MATs in Iraqi businesses over the period of March and April 2021 were examined in this study by using a quantitative methodology. In this research, sampling approach was utilized.Findings: Both inferential and descriptive statistical techniques were utilized to assess the findings of the online survey, which was conducted utilizing surveys from the target population. It is clear from the limited usage of sustainability measures in management accounting that firms in Iraq do not completely integrate sustainability issues into their management accounting systems. The vast majority of businesses use at least one strategy from each of the three categories—inclusive, social, and greenResearch, Practical & Social implications: MAT is used for a variety of purposes including, but not limited to, external reporting, internal compliance monitoring, and to some extent internal decision-making.Originality/value: This study is among the earliest to investigate if it is feasible for Iraq to sustain its external debt financially using an econometric method.